On the Response of Economic Aggregates to Monetary Policy Shocks - Zainab Jehan; Abdul Rashid (Economics and Econometrics Research Institute (EERI), 2011)
This study empirically investigates how shocks to monetary policy measures (short-term nominal interest rate and broad money supply) affect economic aggregates: output growth, price levels and nominal exchange rate. The study is carried out for Pakistan using quarterly data covering the period from 1980 to 2009. In doing this, Johansen's (1988) co integration technique and vector error correction model are applied to explore the long-run relationship among the variables. We find significant evidence on the existence of a long-run stable relationship between our monetary measures and economic aggregates. The impulse response functions (IRFs) are computed to examine the response of each macroeconomic variable to a standard deviation shock to monetary measures. The IRF graphs reveal a price puzzle in closed as well as in open economy model. However, an initial appreciation of exchange rate is observed, indicating the overshooting hypothesis phenomenon for Pakistan.
Keywords: C3; E4; E5; 330; Monetary Policy; Economic Aggregates; VECM; Impulse Response Function